An experimental study of liquid micro-jets produced with a gas dynamic virtual nozzle under the influence of an electric field - Zupan, Bor; Peña-Murillo, Gisel Esperanza; Zahoor, Rizwan; Gregorc, Jurij; Šarler, Božidar; Knoška, Juraj; Gañán-Calvo, Alfonso M.; Chapman, Henry N.; Bajt, Saša (Frontiers in Molecular Biosciences, 2023)
The results of an experimental study of micro-jets produced with a gas dynamic virtual nozzle (GDVN) under the influence of an electric field are provided and discussed for the first time. The experimental study is performed with a 50 % volume mixture of water and ethanol, and nitrogen focusing gas. The liquid sample and gas Reynolds numbers range from 0.09 - 5.4 and 0 - 190, respectively. The external electrode was positioned 400 - 500 μm downstream of the nozzle tip and an effect of electric potential between the electrode and the sample liquid from 0 - 7 kV was investigated. The jetting parametric space is examined as a function of operating gas and liquid flow rates, outlet chamber pressure, and an external electric field. The experimentally observed jet diameter, length and velocity ranged from 1 - 25 μm, 50 - 500 μm and 0.5 - 10 m/s, respectively. The jetting shape snapshots were processed automatically using purposely developed computer vision software. The velocity of the jet was calculated from the measured jet diameter and the sample flow rate. It is found that micro-jets accelerate in the direction of the applied electric field in the downstream direction at a constant acceleration as opposed to the standard GDVNs. New jetting modes were observed, where either the focusing gas or the electric forces dominate, encouraging further theoretical and numerical studies towards optimized system design. The study shows the potential to unlock a new generation of low background sample delivery for serial diffraction measurements of weakly scattering objects.